STRATEGI HUBUNGAN PELANGGAN (CUSTOMER RELATIONSHIP COMMUNICATION) DALAM PENGELOLAAN PLATFORM DAKWAH DIGITAL - Fauzi, Rifqi (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
The rapid growth of digital da’wah platforms has created an urgent need for systematic and well-structured customer relationship management. One communication feature that plays a significant role in maintaining user engagement is push notifications, utilized by applications such as Muslim Pro as a primary interaction channel between the platform and its users. However, the effectiveness of push notifications as a customer communication instrument in the context of digital da’wah still requires deeper examination, particularly concerning user perceptions and responses within academic communities.This study aims to examine the customer relationship communication strategies implemented through push notifications in the Muslim Pro application and to analyze how this feature influences user engagement and loyalty among students of Universitas Islam Bunga Bangsa Cirebon (UIBBC). The research employs a qualitative approach using a case study method and in-depth interviews with twelve informants selected through purposive sampling.The findings reveal that push notifications in Muslim Pro do not merely function as reminders for prayer times but have evolved into a relational communication tool that fosters users’ spiritual connection with the platform. Three dominant strategies were identified: content personalization based on time and location, empathetic framing of da’wah messages, and consistency in notification scheduling that creates an Islamic digital habitus.These findings imply that an effective customer relationship communication approach can strengthen user loyalty within the ecosystem of digital da’wah platforms.Keywords: Reconstruction, Self-Disclosure, Islamic Counseling, Social Media